Heterogeneous photocatalytic (slurry and immobilized) and photo-Fenton (using Foundry Sand) degradation studies of 2-Chloro-4-nitrophenol - Aggarwal, Kashish (My University, 2015)
present study deals with degradation and mineralization of 2Cl4NP through advanced oxidation processes (AOPs) including heterogeneous photocatalysis with suspended and supported TiO2 and heterogeneous solar photo-Fenton process. In heterogeneous slurry photocatalysis the effect of different operating parameters like amount of catalyst, oxidant, pH, A/V ratio and UV intensity were studied whereas effect of foundry sand concentration, oxidant addition as well as iron leaching were studied in solar photo-Fenton process for the degradation of 2Cl4NP. Cement and clay beads were prepared as support materials for TiO2 immobilization for studying fixed-bed photocatalytic degradation of 2Cl4NP. Foundry Sand (FS) was used as an alternate iron source in heterogeneous solar photo-Fenton process as SEM-EDS analysis of FS showed the presence of iron in sufficient amount to act as a catalyst in the degradation process. Degradation of 2Cl4NP was analyzed through UV-Visible spectrophotometer at 266 nm and HPLC. In slurry photocatalysis, 97.19% degradation of 2Cl4NP was achieved in 210 min at optimized conditions of C0=50 mgL-1, pH=4, 0.15 g TiO2 and H2O2= 0.1 mL. The degradation of 68% and 52% of 2Cl4NP was attained in fixed-bed photocatalysis using cement and clay beads respectively and efficacy of cement and clay beads was checked and durability studies of cement and clay beads were carried out. In heterogeneous solar photo-Fenton process 97.19% degradation was obtained in 105 min at optimized conditions of FS= 0.1 g, H2O2=0.05 mL and pH=3. Complete mineralization of 2Cl4NP was confirmed through reduction in COD along with the disappearance of parent compound peak in HPLC chromatograms.
M.Tech (EST) Dissertation
Keywords: Heterogenous; Photocatalysis; Photo-fenton; Chloronitrophenol; energy and environment; energy and environmental science; SEE